Carbon assimilation and distribution in cotton photosynthetic organs is a limiting factor affecting boll weight formation under drought - Zou, Jie; Hu, Wei; Loka, Dimitra A.; Snider, John L.; Zhu, Honghai; Li, Yuxia; He, Jiaqi; Wang, Youhua; Zhou, Zhiguo (Frontiers in Plant Science, 2022)
Previous studies have documented cotton boll weight reductions under drought, but the relative importance of the subtending leaf, bracts and capsule wall in driving drought-induced reductions in boll mass has received limited attention. To investigate the role of carbon metabolism in driving organ-specific differences in contribution to boll weight formation, under drought conditions. Controlled experiments were carried out under soil relative water content (SRWC) (75 ± 5)% (well-watered conditions, control), (60 ± 5)% (moderate drought) and (45 ± 5)% (severe drought) in 2018 and 2019 with two cultivars Yuzaomian 9110 and Dexiamian 1. Under severe drought, the decreases of photosynthetic rate (Pn) and carbon isotope composition (δ13C) were observed in the subtending leaf, bract and capsule wall, suggesting that carbon assimilation of three organs was restricted and the limitation was most pronounced in the subtending leaf. Changes in the activities of sucrose phosphate synthase (SPS), sucrose synthase (SuSy), invertases as well as the reduction in expression of sucrose transporter (GhSUT1) led to variabilities in the sucrose content of three organs. Moreover, photosynthate distribution from subtending leaf to seeds plus fibers (the components of boll weight) was significantly restricted and the photosynthetic contribution rate of subtending leaf to boll weight was decreased, while contributions of bracts and capsule wall were increased by drought. This, in conjunction with the observed decreases in boll weight, indicated that the subtending leaf was the most sensitive photosynthetic organ to drought and was a dominant driver of boll weight loss under drought. Therefore, the subtending leaf governs boll weight loss under drought due to limitations in carbon assimilation, perturbations in sucrose metabolism and inhibition of sucrose transport.